2010
DOI: 10.5004/dwt.2010.1400
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of vacuum membrane distillation for desalination by using a flat sheet membrane

Abstract: Vacuum membrane distillation (VMD) process received a great deal of attention by many investigators because of its promising applications in several separation areas. It is a rising technology for seawater or brine desalination process. The process simply consists of a flat sheet hydrophobic microporous PTFE membrane and diaphragm vacuum pump without a condenser for the water recovery or trap. In this work, VMD performance was investigated for aqueous NaCl solution. In order to enhance the performance of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…They indicated that a pre-treatment step to remove organic matters is essential to prevent membrane fouling. Moreover, other MD configurations are potentially used for desalination when considering various points of view [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that a pre-treatment step to remove organic matters is essential to prevent membrane fouling. Moreover, other MD configurations are potentially used for desalination when considering various points of view [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…DI water readily absorbs salts, and is even known to leach salts from surroundings [121]. Mericq et al [109] for example, completely restored membrane flux using RO permeate water to remove and re-dissolve scale deposits from synthetic seawater in their VMD system.…”
Section: Membrane Cleaningmentioning
confidence: 99%
“…Fisher's least significant difference (LSD) method is similar to Tukey's method in principle, the differences in response averages (permeate flux in this work) are compared to a corresponding LSD value that is represented in Eq. (9). This method uses the t-statistic calculated using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the SGMD, condensation takes place outside the membrane cell and heat loss by conduction is insignificant [8]. VMD is used to separate volatile compounds from water and is effective in desalination of sea water [9].…”
Section: Membrane Distillation Configurationsmentioning
confidence: 99%